(untitled) (Research, Society and Development, 2020)
Introduction: Prenatal care should be performed to detect the risks of a pregnancy early, thus preventing future complications. The nurse plays an extremely important role in care during the pregnancy and childbirth cycle, as it acts in the health education process, guiding the woman and her family according to the changes during this process, thus obtaining higher quality care. Objective: To identify through the scientific literature the role of nurses in prenatal consultations in primary care. Methodology: This is a study with a qualitative approach, of the integrative review type, whose database was the Virtual Health Library (VHL). Complete articles in Portuguese published between 2011 and 2020 were selected. At the end of the application of the previously described criteria, 5 articles emerged that proceeded to a thorough reading for analysis of the results. Results: In the data analysis, two thematic categories were established: Pregnancy and Prenatal Care in Primary Health Care. Conclusion: The research led us to conclude that starting prenatal care early can reduce the risks of morbidity and mortality. Nurses have an essential role in the elaboration of the bond between the team, the patient and the family, ensuring comprehensive care, shared autonomy and accessibility to services.